A field survey of BFDV in wild populations of Cyanoramphus parakeets in New Zealand and Norfolk Island : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology, Massey University, New Zealand - Wallace, Connor James (Massey University, 2022)
Psittaciformes is one of the most at-risk orders of birds, with 28% of parrot species being threatened with extinction as of 2016. Major threats to parrots include deforestation and habitat loss, predation by invasive mammals and poaching for the pet trade and collectors. Pathogens and disease are also a significant threat, particularly for species that are isolated, genetically depauperate and already at risk of extinction. Two parrot species that meet these conditions are the kākāpō (Strigops habroptilus) of New Zealand and the Norfolk parakeet (Cyanoramphus cookii) of Norfolk Island. Beak and feather disease virus (BFDV) stands out as a pathogen of concern for parrot conservation, with a global distribution, the ability to be transmitted between a wide range of parrot species and the potential to cause chronic and lethal infections. This thesis presents the results of testing 20 kākāriki (Cyanoramphus spp.) sympatric with kākāpō on Codfish Island/Whenua Hou from samples collected in 2019-2021 and 51 Norfolk parakeets sampled in 2015 for BFDV. This testing was conducted through PCR. BFDV was not detected in the kākāriki feather samples but four of the Norfolk parakeet samples tested positive for the virus. This is the most recent detection of BFDV in the sole population of Norfolk parakeets and the first to do so through PCR screening. The sample size of 20 kākāriki was determined to be insufficient to substantiate freedom from BFDV on Codfish Island. This thesis explores and discusses these findings in the context of other published studies to make conservation recommendations for the kākāpō and Norfolk parakeet with respect to BFDV and other pathogens of concern. Approaches to disease biosecurity and opportunities for future study are also discussed based off of the data presented and inspired by the challenges this study faced due to the global COVID-19 pandemic and ensuing national and regional lockdowns in New Zealand in 2021. Attached as an appendix is a scientific article that I helped to prepare for the journal Diversity presenting a retrospective analysis of screening five populations of parrots from Argentina, Australia and New Zealand for BFDV.
Keywords: 310307 Population ecology